Reconstructing Multicultural Education Through Cultural Empathy within the Philosophy of Citizenship - Gultom, Andri Fransiskus (Rhizome : Jurnal Kajian Ilmu Humaniora, 2025)
The increasing complexity of cultural plurality within contemporary universities highlights a pressing problem: multicultural education frequently remains confined to formalistic recognition, without fostering deeper ethical relations among diverse groups. This research aims to reconstruct multicultural education through the lens of cultural empathy, grounding the analysis in the philosophy of citizenship. The research was conducted at Universitas PGRI Kanjuruhan Malang, with university leaders and students as the main subjects. Employing a qualitative approach, examines dialogical encounters, narratives of recognition, and practices of cultural inclusion within the university context. The findings reveal a novelty: cultural empathy operates not merely as an affective disposition but as an epistemic practice that cultivates civic responsibility, and equality. Theoretically, the research advances a philosophical framework that positions multicultural education as a civic-ethical project rather than an administrative program. Practically, it contributes to designing pedagogical strategies that foster dialogical understanding, citizenship ethics, and social cohesion in diverse academic communities. This reconstruction thus situates multicultural education within a broader philosophical discourse, offering new insights for sustaining democratic life in plural societies.